Pengembangan Karakter Komunikatif dan Disiplin melalui Metode Culturally Responsive Teaching dengan Pembelajaran Sosial Emosional pada Pembelajaran Sejarah Siswa Kelas X-2 SMAN 1 Kalitidu - Nasution Nasution; Efhalistiana Dewi; Siti Vivi Rohmawati Qiyarotul Ummah (Journal on Education, 2023)
The learning process often only focuses on the academic results achieved and tends to ignore the ability of character skills in students, one of which is communicative and disciplined character. This research aims to get an overview of the implementation of the culturally responsive teaching approach with social-emotional learning in history learning for class X-2 students of SMAN 1 Kalitidu. The data obtained from this study were in the form of communicative and disciplined characters in students in learning history before and after using this approach. Data sources were obtained from teachers, students, and the implementation of interactions between students and teachers during the learning process. The procedure for carrying out this research used two cycles, in each cycle consisting of observing, processing and taking action. Data collection techniques using observation, documentation, interviews, and reflective journals. Using descriptive analysis techniques. The results of research that has been carried out on students of class X-2 in history learning using the application of a culturally responsive teaching approach with social-emotional learning can be concluded that implementation using this approach can develop communicative and disciplined character. This can be seen through the active involvement of students while participating in learning. This approach makes students have motivation, courage, empathy, a sense of responsibility, can make decisions and are confident in expressing opinions.